PROFESSIONAL EXPECTATIONS OF LITHUANIAN PHYSICAL EDUCATION UNDERGRADUATES - Vainienė, Edita; Rastauskienė, Giedrė Judita; Šukys, Saulius (Acta Paedagogica Vilnensia, 2014)
This paper deals with professional expectations of Lithuanian physical education undergraduates from different fields: rehabilitation, sports, physical education. The study sample consisted of 419 undergraduates from five universities of Lithuania: Sports University, Šiauliai University, University of Educational Sciences, University of Health Sciences, Klaipėda University. This was a statistically representative sampling with a 95-percent certainty. The respondents were divided into groups according to the Ministry of Government Order No. 1749 list of the areas and fields in which studies are offered in higher education institutions. Lithuanian academical studies of physical education can only be implemented as separate study fields: B300 rehabilitation (the medicine and health group of study fields), C600 sport (life sciences group), and X100 pedagogy of physical education (education group of study fields). Theoretical analysis allowed us to construct a questionnaire of 13 statements for the analysis of professional expectations and their links with studies. The factor analysis allowed identifing two expectations’ macro-categories: professional expectations for the future and expectations for the choice of study. The field of study in this research was analysed as an independent variable. We calculated Cramer’s V as a measure of the strength of association among dependent and independent variables. The results have shown that the professional expectations of students from different study fields vary i.e. that expectations as to the choice of study are similar, but professional expectations for the future differ. Undergraduates of the rehabilitation study field foster higher professional expectations for the future than do students from the sports or pedagogy of physical education fields of study. The academic studies aimed at meeting the public needs allow students from the rehabilitation field of study easier to discern the direction of study and professional interface, making it easier for them to draw a contour of the professional self. However, for students of the sports, whose studies are directed towards the academic level and for students of physical education pedagogy, which has a high degree of interdisciplinarity, to do this in the final phase of studies is very difficult. The interdisciplinary profile of a study field is a crucial factor of the for lower professional expectations, and it offers a guideline for the further research.